Influence of School Head Conflict Management, Interpersonal Communication, Work Climate on Teacher Performance in Elementary School District Sector Tabongo - Hamsah, Ripin; Ansar, Ansar; Arifin, Arifin (Darul Yasin Al Sys, 2026)
This study analyzes the influence of principals’ conflict management, interpersonal communication, and work climate on teacher performance in public elementary schools in the Tabongo sub-district. Using a quantitative approach with a correlational design, the research involved a population of all elementary school teachers in the Tabongo sub-district, with the sample selected through proportional random sampling. Data were collected using a questionnaire that had been tested for validity and reliability, and analyzed using multiple linear regression to examine the direct effects of each independent variable on the dependent variable. The results show that (1) principals’ conflict management has a direct positive and significant influence on teacher performance; (2) interpersonal communication has a direct positive and significant influence on teacher performance; (3) work climate has a direct positive and significant influence on teacher performance; (4) principals’ conflict management has a direct positive and significant influence on work climate; and (5) interpersonal communication has a direct positive and significant influence on work climate. These findings indicate that strengthening principals’ capacity in conflict management, enhancing interpersonal communication, and fostering a positive work climate are critical for optimizing teacher performance. The study contributes empirical evidence to the literature on educational management and underscores the importance of school leadership and organizational conditions in improving teacher performance in elementary education settings.